IMPACT OF PSYCHOLOGY IN ART. (International Journal of Engineering Sciences & Management Research, 2015)
Aesthetics in art one of the oldest areas of psychological research after discovery of Sigmund Freud and Carl Jung theory of unconscious mind. They explored the human mind more thoroughly than any other who became before them. This paper discusses the temperament of various artists and their works. The experimental study of evaluations and feelings related to art has a long history in the sphere of psychology. Psychology and its relationship with art played a greater role in the artists’ symbolic works. Emotions and art are intimately related from human civilization to the contemporary period, theories of aesthetics have emphasized the role of art in evoking, shaping, and modifying human feelings. Psychology has had a steady interest in aesthetic problems since Impressionism. The study of art and the study of emotions, as areas of scientific inquiry, both developed during the 19th century as we have seen the artwork of various artists.